Remifentanil Protects against Lipopolysaccharide-Induced Inflammation through PARP-1/NF-κB Signaling Pathway - Jian-ning Zhang; Yang Ma; Xi-yan Wei; Ke-yin Liu; Hao Wang; Hui Han; Yi Cui; Ming-xiang Zhang; Wei-dong Qin (Mediators of Inflammation)
Sepsis is a leading cause of death in patients with severe infection worldwide. Remifentanil is an ultra-short-acting, potent opioid analgesic. In the study, we aimed to investigate the role and underlying mechanism of remifentanil in lipopolysaccharide- (LPS-) induced inflammation in human aortic endothelial cells (HAECs). HAECs were pretreated with phosphate-buffered saline (PBS) or remifentanil (2.5 μM) for 30 min, then stimulated by LPS (10 μg/ml) for another 24 h. Poly(ADP-ribose) polymerase 1 (PARP-1) was inhibited by small interfering RNA (siRNA). Superoxide anion production and DNA damage were analyzed by dihydroethidium (DHE) staining and comet assay. The inducible nitric oxide synthase (iNOS), intercellular adhesion molecule 1 (ICAM-1), PARP-1, poly(ADP-ribose) (PAR), and nuclear factor-kappa B p65 (NF-κB p65) expressions were analyzed by RT-PCR or western blotting analysis. NF-κB p65 nuclear translocation was assessed by immunofluorescence. Compared with the control group, pretreatment with remifentanil significantly reduced superoxide anion production and DNA damage, with downregulation of iNOS, ICAM-1, and PARP-1 expressions as well as PAR expression. Moreover, pretreatment with PARP-1 siRNA or remifentanil inhibited LPS-induced NF-κB p65 expression and nuclear translocation. Remifentanil reduced LPS-induced inflammatory response through PARP-1/NF-κB signaling pathway. Remifentanil might be an optimal choice of analgesia in septic patients.